Microalgae-based biofertilizers improve fertility and microbial community structures in the soil of potted tomato - Xiaotong Song; Jiayi Liu; Yanzhang Feng; Chengxu Zhou; Xiaohui Li; Xiaojun Yan; Roger Ruan; Pengfei Cheng (Frontiers in Plant Science)
Continuous cropping decreases soil nutrients and destroys microbial community structure, so the development of eco-friendly and effective biofertilizers is necessary under present conditions. In this study, the preserving microalgal strain Tribonema sp. (H) was firstly selected to be combined with agroforestry waste (shell powder, straw fermentation liquid) and the agroforestry microorganism Bacillus sp. to form microalgae-based fertilizers for the continuous cropping soil of potted tomato. Compared to the control (CK), microalgae-based fertilizers (concentration: 4.45 × 106 cells/ml, dosage: 20 ml/day) improved soil nutrients and salinization indicators. Specifically, the combination of Tribonema sp. and shell powder (HB) reduced electrical conductivity (EC) by 33.7% and significantly increased the Ca2+ content by 59.4%; Tribonema sp. and Bacillus sp. (HY) improved the effects of available phosphorous (AP), DOC, DON, NH4+-N, NO3−-N, and Mg2+ in the soil by 27.4%, 231.3%, 403.4%, 125.2%, 215.6%, and 73.4%, respectively. Microalgae-based fertilizers alter the abundance of soil bacteria and fungi, causing beneficial bacteria such as Thermonaerobaculia, Subgroup_10, Sordariomycetes, and Microascaceae to increase, while pathogenic bacteria like Pseudomonas, Togniniaceae, and Phaeoacremonium decreased. Combining microalgae with agroforestry wastes as a biofertilizer is promising to improve the microbial community structure of the soil with continuous cropping, which will aid in the increase of tomato production and promote green agricultural development.